ASUHAN KEBIDANAN KOMPREHENSIF PADA NY. “E” UMUR 24 TAHUN DI POLINDES MELATI BIDAN “N” DESA TUGUSUMBERJO KABUPATEN JOMBANG - Nanda Yuliana; Najah Soraya Niah; Rista Dian Anggraini (Literasi Kesehatan Husada: Jurnal Informasi Ilmu Kesehatan, 2023)
Introduction: The National Maternal Mortality Rate is 305 per 100,000 live births. In 2019, the Maternal Mortality Rate for East Java Province reached 89.81 per 100,000 live births. This figure has increased compared to 2020 which reached 98.39 per 100,000 live births. The most common causes of maternal death in Indonesia in 2019 are bleeding, hypertension in pregnancy, infections, metabolic disorders, and others (RI Ministry of Health, 2019). Around 25-50% of maternal deaths are caused by problems related to pregnancy, childbirth and the puerperium (WHO, 2018). Objectives: The purpose of conducting this research is to provide Comprehensive Midwifery Care for Ny. E is 24 years old at the Melati Midwife Polindes "N" in Tugu Sumberjo Village, Peterongan District, Jombang Regency and documentation with SOAP. Method: This type of case study using the descriptive method was carried out at the Melati Midwife Polindes "N" in March - June 2022. The subject matter was Mrs. “E” aged 24 years with data collection techniques using a physical examination. interviews and observations as well as midwifery care forms, client MCH books, client laboratory results sheets. Results: After midwifery care for Mrs. "E" aged 24 years, the mother was in good health and had no complaints from pregnancy, childbirth, newborns (BBL), postpartum and family planning (KB). Conclusion: There is no gap between theory and practice starting from subjective data, objective data and management. In the case of Mrs. “E” aged 24 years.